Bone dust and diced cartilage combined with blood glue: A practical technique for dorsum enhancement - Örero?lu, Ali Rıza; Çakır, Barış; Akan, Mithat (Springer, 2014)
The combination of dorsal nasal reconstruction and camouflage of surface irregularities is an important step in rhinoplasty. We hereby present our technique of delivering diced cartilage in combination with bone dust to the nasal dorsum using the patient's blood as a carrier. We advocate use of an autologous material (blood) as a scaffold for graft delivery, dismissing the use of a foreign material or fascial wrapping of the graft. Using the patient's blood for this purpose not only stabilizes the graft into a malleable structure that is easily applicable to the nasal dorsum, it also decreases the potential for reaction against foreign material. Level of Evidence V: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.
Keywords: Blood Glue; Bone Dust; Diced Cartilage; Dorsal Camouflage; Nasal Dorsum Enhancement